Exploring the Correlation Between Peer Interaction and Self-Esteem in Early Childhood: A Study of 5–6-Year-Olds in Indonesian Kindergartens - Nuzulia Rizkika Wahyudyanti; Anayanti Rahmawati (AL-ISHLAH: Jurnal Pendidikan, 2025)
Self-esteem plays a critical role in early childhood development, influencing social competence, emotional well-being, and peer relationships. Given the increasing recognition of socio-emotional development in kindergartens, this study investigates the relationship between peer interaction and self-esteem in children aged 5–6 years. A quantitative correlational design was used, involving 100 kindergarten children selected through cluster random sampling from four schools in Banjarsari District, Surakarta. Data were collected using teacher-rated questionnaires adapted from validated instruments. The peer interaction scale consisted of 36 items (Cronbach’s α = 0.983), and the self-esteem scale included 7 valid items (Cronbach’s α = 0.762). Statistical analysis was conducted using the Pearson Product Moment correlation in SPSS 27. The analysis showed a significant positive correlation between peer interaction and self-esteem (r = 0.593, p 0.001), indicating a moderate relationship. Most children fell into the medium category for both peer interaction (65%) and self-esteem (62%). Boys showed slightly higher averages in both variables compared to girls. The findings support theoretical perspectives, including Vygotsky’s and Erikson’s views on socio-emotional development, emphasizing the importance of peer interaction in shaping children’s self-concept. While the study provides useful insights for educators and parents, its generalizability is limited due to its localized sample and reliance on teacher-reported data. Future research is recommended to adopt longitudinal designs and include observational or multi-informant assessments.